PENGARUH KEGIATAN BERMAIN KREASI MOZAIK DENGAN WALLPAPER TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK E-SCHOOL - Mardiana Mahmuddin; Parwoto; Sitti Nurhidayah Ilyas (UIR PRESS, 2021)
The purpose of this study was to determine the effect of creative play activities mosaic using wallpaper material on motor skills smooth in children aged 5-6 years in e-school Kindergarten. Types of research This is research. The approach used in this research is quantitative approach with the type of research Quasi Experiment Design. Subject This research is children aged 5-6 years Kindergarten e-school. Object This research is fine motor ability. Data collection technique using descriptive analysis techniques and statistical analysis techniques nonparametric. The results showed that fine motor skills children aged 5-6 years in e-school Kindergarten can be improved through Mosaic creation play activities